Characterization of Liquid Water Saturation in Gas Diffusion Layers by X-Ray Tomographic Microscopy. Issue 3 (23rd December 2015) - Lamibrac, A.; Roth, J.; Toulec, M.; Marone, F.; Stampanoni, M.; Büchi, F. N.
Abstract : Performance and durability of polymer electrolyte fuel cells are closely related to the water management. In gas diffusion layers (GDL), the presence of liquid water is associated with mass transport losses. For optimization of the materials, mechanisms and parameters influencing the water saturation have to be understood. Ex-situ water injection and withdrawal experiments, allowing for well-defined boundary conditions, have been performed with three different GDL materials, using X-ray tomographic microscopy to image the liquid water phase on the pore scale of the materials. The liquid saturation in the GDLs has been imaged as function of the capillary pressure. The results reveal that, due to the anisotropic structure of the GDLs, transport of water occurs mainly in the through-plane direction via parallel water paths. When the GDL is coated with a microporous layer (MPL), liquid saturation requires higher capillary pressure to overcome the MPL/GDL mixed region where pore and throat sizes are reduced and the water paths are restricted to the crack regions of the MPL.